Problems, Principles and Prospects of English Studies in an African University - Afolayan, Adebisi (University of Ife Press, 2013)
The English language is today the most international of all languages. To acquire it is to possess one of the most efficient keys to the storehouse of human achievements. English studies, therefore, as a discipline cannot but mean the academic pursuit or the search for truth about the most ubiquitous tool. It simply follows from our hypothesis that English studies must be irreducible to simple, straight forward propositions and concepts.